2021
DOI: 10.1007/s40558-021-00199-1
|View full text |Cite
|
Sign up to set email alerts
|

Travel live streaming: an affordance perspective

Abstract: This study draws on tourism literature and current examples to propose that the emergence of Travel Live Streaming (TLS) provides new affordances for live streamers, viewers, and sponsors. Despite its increasing popularity and the new opportunities for communication and marketing in tourism, TLS has received limited attention in the academic literature. The aim of this paper is to use affordances theory to understand some of the key features and benefits of TLS. It is argued that TLS affordances include tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 78 publications
(81 reference statements)
0
33
0
1
Order By: Relevance
“…Previous studies have shown that e-commerce live streaming consumer' purchase intentions can be influenced by live streaming strategy (Zhang et al, 2020), interaction (Li et al, 2021;Zhang et al, 2021b), and social presence (Ang et al, 2018;Chen and Liao, 2022). However, previous studies have mostly studied the impact of one feature of e-commerce live streaming on consumer' purchase intention, without systematic and comprehensive studies, and they have not connected live streaming features with consumers' perception (Sun et al, 2019;Deng et al, 2021;Qiu et al, 2021;Lin et al, 2022). This study confirmed that interactivity and authenticity of the tourism e-commerce live streaming features have positive effects on consumers' purchase intention, but entertainment has insignificant effect on consumers' purchase intention.…”
Section: Research Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that e-commerce live streaming consumer' purchase intentions can be influenced by live streaming strategy (Zhang et al, 2020), interaction (Li et al, 2021;Zhang et al, 2021b), and social presence (Ang et al, 2018;Chen and Liao, 2022). However, previous studies have mostly studied the impact of one feature of e-commerce live streaming on consumer' purchase intention, without systematic and comprehensive studies, and they have not connected live streaming features with consumers' perception (Sun et al, 2019;Deng et al, 2021;Qiu et al, 2021;Lin et al, 2022). This study confirmed that interactivity and authenticity of the tourism e-commerce live streaming features have positive effects on consumers' purchase intention, but entertainment has insignificant effect on consumers' purchase intention.…”
Section: Research Implicationsmentioning
confidence: 99%
“…For example, facial recognition and smart cameras were used in gambling industry (Liu et al, 2021b), digital technology was applied in hospitality industry in Macao (Liu et al, 2021c), and live streaming was used in tourism industry (Liu et al, 2022). Tourism e-commerce live streaming is developing rapidly (Deng et al, 2021;Xie et al, 2022). In China, online travel agents (OTAs), such as Ctrip, Mafengwo, and Tuniu, are accelerating the development of live streaming and exploring the business model innovation of "tourism + live streaming" through e-commerce live streaming and virtual tourism, such as the "Boss Live Session" activity initiated by Ctrip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Travel live stream also existed before, and "can be viewed as a product where the boundaries of tourism experience are negotiated and challenged to establish a new genre of interactive digital tourism." (Deng, 2021). Despite being increasingly adopted by the tourism industry, particularly in Asian destinations (e.g., China, South Korea, and Japan), academic research has paid little attention to live streaming in relation to tourism.…”
Section: New Ways Of Travelling: Interactive Digital Tourismmentioning
confidence: 99%
“…2) transmisja strumieniowa na żywo (live-streaming broadcasting) -dla miast turystycznych stała się nowym kanałem tworzenia i rozpowszechniania doświadczeń podróżniczych oraz promowania destynacji (Deng, Benckendorff , Wang 2021). Odwiedzający z całego świata mogą cieszyć się scenerią w czasie rzeczywistym, m.in.…”
Section: Wspieranie Innowacji Bazujących Na Nowych Technologiachunclassified